2015
DOI: 10.5195/mitrip.2014.46
|View full text |Cite
|
Sign up to set email alerts
|

Are Aspects of a Motivational Interview Related to Subsequent Changes in Physical Activity and Regulatory Style? Examining Relationships among Patients with Rheumatoid Arthritis

Abstract: Objectives: To determine whether the integrity of motivational interviewing (MI) delivery relates to short-term changes in physical activity (PA) and regulatory style within a sample of patients with rheumatoid arthritis, and to examine whether therapist proficiency in MI improves over time. Methods:During a randomized controlled trial to promote PA, 27 patients received a motivational interview from one of three trained physical therapists, which was coded with the Motivational Interviewing Treatment Integrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Our findings for PA are in line with research showing that MI, in general, is an important predictor for intervention effects [42]. Also, other research revealed that MI adherent counseling behaviors were associated with increases in PA behavior [43,44].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings for PA are in line with research showing that MI, in general, is an important predictor for intervention effects [42]. Also, other research revealed that MI adherent counseling behaviors were associated with increases in PA behavior [43,44].…”
Section: Discussionsupporting
confidence: 91%
“…During the consultations, HCPs made efforts to adhere to the spirit of MI and use MI-adherent behaviors such as obtaining permission before providing advice or information, affirming the patient, emphasizing the patient’s control, and supporting the patient with compassion or sympathy [ 39 ]. In addition, HCPs were instructed to avoid MI nonadherent behaviors such as advising without permission; confronting the patient; or directing the patient by giving orders, commands, or prescriptions [ 39 ], as a positive balance between MI-adherent and MI-nonadherent behaviors has been shown to predict favorable outcomes in consultations about PA behavior changes [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%